Culture, Identity and Care for Nature - Maia, Juliana Capra (Sustainability in Debate, 2015)
This paper has been written focusing two connected questions relating Dumont’s theories to Brazilian reality. Firstly, it investigates whether Brazilian and modern western societies ”“ specially the American society ”“ see nature through the same lenses. Second, it discusses whether, in Brazil, an anthropocentric and utilitarian reasoning is favoured at the expense of the biocentric and ethical arguments in defence of wilderness. Both questions are answered through bibliographical research in the general and Brazilian history fields. This paper corroborates Da Matta’s thesis according to which nature is inserted into the Brazilian social hierarchy and there is no rupture between nature and culture in the country. Due to this position of nature into the social hierarchy, anthropocentric, utilitarian and conservationists arguments tend be more influential than the biocentric, ethical and preservationist ones.